Aquatic macrophytes: ecological features and functions - M. S. Lesiv (Біологічні студії, 2020)
The article is devoted to the analysis of current data on the ecological features and functions of the aquatic macrophytes which are important components of aquatic and wetland ecosystems across the globe. Macrophytes comprise a taxonomically diverse group of macroscopic plants including representatives of vascular aquatic plants, bryophytes, as well as green macroalgae and charophytes. An assemblage of macrophytic vegetation consists of emergent species whose vegetative parts emerge above the water surface, submerged and floating species, with each ecological group having specific features in morphology and physiological processes. A wide range of the adaptive mechanisms developed by aquatic macrophytes at the morphological, physiological, and biochemical levels enables them to inhabit various types of freshwater, brackish-water, and marine habitats. Macrophytes are an important component of aquatic food webs and perform a host of ecological functions in water ecosystems. The main ones are synthesis and storage of organic compounds and oxygen release, absorption and accumulation of chemical elements, water filtration and detoxification of pollutants, release of biologically active compounds involved in interspecies communications, provision of food, shelter and feeding places for aquatic animals, impact on the hydrological regime of water bodies, etc. A wide array of macrophyte species aresed in various human activities, including bioindication of water quality, phytoremediation of contaminated water bodies and wastewater treatment. However, human activities leading to surface water pollution, eutrophication and global warming have led to a concomitant decrease in macrophyte diversity in many freshwater ecosystems and in marine environment. Therefore, proper management of aquatic and wetland ecosystems, including their monitoring and control, is a prerequisite for a successful conservation of habitats and species richness of the aquatic macrophytes.